2020
DOI: 10.1016/j.jvb.2019.103365
|View full text |Cite
|
Sign up to set email alerts
|

Testing the structure of the Career Decision-Making Difficulties Questionnaire across country, gender, age, and decision status

Abstract: Many individuals face difficulties when making a career decision. Gati, Krausz, and Osipow (1996) proposed a taxonomy that classifies career decision-making difficulties into three major clusters, which are further subdivided into 10 categories. Based on the proposed taxonomy, they developed the Career Decision-making Difficulties Questionnaire (CDDQ), which has been since adopted and used in more than 50 countries. Despite its widespread use, the dimensionality of the CDDQ has not yet been fully demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 64 publications
(122 reference statements)
6
63
0
7
Order By: Relevance
“…The authors have constructed an instrument (Career Decision Making Difficulties Questionnaire) to measure difficulties in the career decision-making process. A very recent extensive study (Levin, Braunstein, Lipshits-Braziler, Gati, & Rossier, 2020) confirmed the internal structure of this instrument, its reliability and scalar invariance in seven English-speaking countries. Similar findings regarding the proposed structure and reliability were found in other studies conducted among high school students (e.g.…”
Section: Structure Of the Career Indecisionmentioning
confidence: 64%
“…The authors have constructed an instrument (Career Decision Making Difficulties Questionnaire) to measure difficulties in the career decision-making process. A very recent extensive study (Levin, Braunstein, Lipshits-Braziler, Gati, & Rossier, 2020) confirmed the internal structure of this instrument, its reliability and scalar invariance in seven English-speaking countries. Similar findings regarding the proposed structure and reliability were found in other studies conducted among high school students (e.g.…”
Section: Structure Of the Career Indecisionmentioning
confidence: 64%
“…According to the results of the research conducted by Spitzer (2000), the levels of self-regulation and intrinsic motivation related to career processes of elderly students were found to be higher than younger students. According to the results of Levin et al (2019), it was found that the career decision making skills of the participants aged 19-24 were higher than those of the younger participants. According to the results of the study conducted by Hirschi et al (2015), no relationship was found between the participants' career adaptation skills of the age variable.…”
Section: Discussionmentioning
confidence: 96%
“…Имено, се базира на претходно споменатата и теориски заснована таксономија на тешкотиите во процесот на донесување одлука поврзана со кариерата и е најнов инструмент во оваа област. Во мошне скорешна опсежна студија (Levin, Braunstein, Lipshits-Braziler, Gati, & Rossier, 2020) потврдени сe интерната структура на овој инструмент, неговата релијабилност и скаларна инваријанса во седум земји каде се зборува англискиот јазик. Слични наоди во поглед на предложената структура и релијабилноста се најдени и во други студии спроведени кај средношколци (на пр.…”
Section: структура на неодлучноста при изборот на кариераunclassified
“…Од друга страна, таа може да се манифестира како долгорочна, хронична состојба на нерешителност. Левин и соработниците (Levin et al, 2020) соопштуваат дека изворите на кариерната неод-лучност од когнитивна природа постепено се намалуваат одејќи од адолесцентниот кон периодот на зрелост, а пак, тешкотиите што произлегуваат од емоционални фактори и од личноста стануваат поизразени движејќи се од адолесценција кон зрелост што може да биде делумна поддршка за дистинкцијата помеѓу неодлучноста (indecision) и нерешителноста (indecisiveness).…”
Section: заклучокunclassified